PENGARUH KELENGKAPAN BARANG DAN HARGA TERHADAP MINAT BELI PADA ALFAMART SADITAN DI KABUPATEN BREBES - Solikhin Solikhin (Sekolah Tinggi Ilmu Ekonomi Widya Manggalia, 2017)
ABSTRACT The purpose of this study is: To find out whether the completeness of goods and prices influence the buying interest in Alfamart Saditan in Brebes Regency. From the results of the analysis concluded as follows: The calculation results that the tcount test using a confidence level of 95 percent (α / 2 = 0.05 / 2 = 0.025) and the degree of freedom Nk (100-2) obtained t table of 1.984 and the results of calculations on SPSS shows X1 = 2,620 which means that t count> t table. This shows that Ho is rejected or the completeness of the goods significantly affects the interest in buying at Alfamart Brebes. While at X2 obtained 2,276 which means that t count> t table. This shows that Ho is rejected or the price significantly affects the interest in buying at Alfamart Brebes. The results of these calculations can be concluded that partially the variable completeness of goods and prices have a significant effect on the variables of interest in buying at Alfamart Brebes. From the results of these calculations, it can be made an equation Y = 20,657 + 2,022 X1 + 1,117 X 2. From this equation it can be explained that the constant value is 20,657 which means that if the variable completeness of goods and prices are ignored then buying interest in Alfamart Brebes is 20,657 units. While the variable completeness of goods (X1) obtained a value of 2.022, which means that if the variable completeness of goods is increased by one unit, the interest in buying at Alfamart Brebes will increase by 2,022 units times. In the price variable (X2) the value is 1.117 which means that if the price variable is increased by one unit, the interest in buying at Alamart Brebes will increase by 1.117 units times Keywords: completeness of goods, price and purchase value